2011
DOI: 10.2478/v10026-011-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior of Pb(II) onto xanthated rubber (Hevea brasiliensis) leaf powder

Abstract: A plant waste, rubber (Hevea brasiliensis) leaf powder was modifi ed with carbon disulfi de (xanthation) for the purpose of introducing sulfur groups, and the adsorbent performance in removing Pb(II) ion was evaluated. Pb(II) adsorption was confi rmed by spectroscopic analysis, which involved Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The amount of Pb(II) adsorbed increased with increasing pH, contact time and concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The adsorption process strongly followed toward the pseudo-secondorder model, indicating the chemisorption may be rate limiting in the adsorption of mistletoe leaves for Pb(II) and Cd(II). Similar trend has been also observed in the studies of the adsorption of Cd(II) on Terminalia catappa linn leaf powder [50], adsorption of cadmium (II) and lead(II) ions onto Ficus cassia leaves [28], adsorption of copper(II) on dry fruit product [51], and adsorption of Cu(II) on peat [32]. Their data have suggested that the pseudo-second-order model provides the best correlation data for the rate-limiting step that may be sorption or chemical sorption involving valence forces through sharing or exchange of electron between sorbent and sorbate.…”
Section: Adsorption Kineticsupporting
confidence: 75%
“…The adsorption process strongly followed toward the pseudo-secondorder model, indicating the chemisorption may be rate limiting in the adsorption of mistletoe leaves for Pb(II) and Cd(II). Similar trend has been also observed in the studies of the adsorption of Cd(II) on Terminalia catappa linn leaf powder [50], adsorption of cadmium (II) and lead(II) ions onto Ficus cassia leaves [28], adsorption of copper(II) on dry fruit product [51], and adsorption of Cu(II) on peat [32]. Their data have suggested that the pseudo-second-order model provides the best correlation data for the rate-limiting step that may be sorption or chemical sorption involving valence forces through sharing or exchange of electron between sorbent and sorbate.…”
Section: Adsorption Kineticsupporting
confidence: 75%